The Effect of Simvastatin on Nitric Oxide and hs-CRP Levels in patients with Liver Cirrhosis at Dr. Moewardi Hospital, Surakarta - Hariyanto, Budhi; Kusnanto, Paulus; Purwanto, Bambang (Indonesian Journal of Medicine, 2019)
Background: The prevalence of liver cirrhosis (SH) worldwide is at seventh place as the cause of death. Increased pressure in the portal vein Portal Hypertension (HP) causes esophageal varices and the more likely the patient to bleed. Endothelial dysfunction in cirrhosis of the liver causes a decrease in nitric oxide (NO) levels resulting in an imbalance between relaxation factors and portal vein contractions and increasing hs-CRP levels. Simvastatin can increase NO levels and improve endothelial dysfunction in patients with SH and can reduce levels of hs-CRP. This study aimed to determine the effect of simvastatin administration on nitric oxide and hs-CRP level in patients with liver cirrhosis.Subjects and Method: This was a randomized controlled trial conducted at Dr. Moewardi hospital, Surakarta, Central Java. A sample of 29 patients was divided into treatment and control groups. 14 patients in the treatment group were given simvastatin dose of 20 mg. 15 patients in the control group received a placebo. The dependent variable was a nitric oxide and hs-CRP levels. The independent variable was Simvastatin administration. Nitric oxide serum level was measured by an enzyme-linked immunosorbent assay (ELISA). Hs-CRP level was measured by the immunechemiluminescent method. The data were analyzed by t-test.Results: NO level after Simvastatin 20 mg administration (Mean= 7.93 µg/mL; SD= 1.78 µg/ mL) was higher than before (Mean= 5.14 µg/mL; SD= 2.25 µg/mL) and it was statistically significant (p = 0.001). Hs-CRP level after Simvastatin 20 mg administration (Mean= 2.04 mg/L; SD= 0.80 mg/L) was lowered than before (Mean= 7.82 mg/L; SD= 1.15 mg/L) and it was statistically significant (p= 0.001).Conclusion: Simvastatin administration increases NO serum levels and reduces the hs-CRP level in patients with liver cirrhosis.Keywords: nitric oxide, hs-CRP, simvastatin, liver cirrhosisCorrespondence: Budhi Hariyanto. Masters Program in Family Medicine, Universitas Sebelas Maret. Jl. Ir Sutami 36A, Surakarta 57126, Centra Java. Email: antohariyanto787@gmail.com. Mobile: 082328010442.Indonesian Journal of Medicine (2019), 4(1): 9-14https://doi.org/10.26911/theijmed.2019.04.01.02